STUDIES ON THE ANTI-INFLAMMATORY EFFECT OF THE AQUEOUS EXTRACT OF THE LEAVES OF VITEX TRIFOLIA L. IN ALBINO RATS. - A. PFUZIA; R.K. BHARATI DEVI; KH. SHARATCHANDRA; B. N. DEBASHREE; BANYLLA SN; KH. SANIA MONICA (International Journal of Pharma and Bio Sciences, 2013)
Vitex trifolia belongs to the family lamiaceae. The anti-inflammatory property of the aqueous extract of the leaves of Vitex trifolia L. was studied by carrageenan induced paw oedema, granuloma pouch and formaldehyde induced arthritis method. in albino rats. The extract was administered at the varying doses of 500, 1000 & 2000 mg/kg body weight per orally to three groups of six animals each. Increasing the doses of the test drug produced signicant (p<0.001) increased in percentage of inhibition of paw oedema and significant inhibition of exudate formation. The extract shows significant anti-inflammatory activity when compared with the control and comparable efficacy with the standard. The present study suggests that the aqueous extract of the leaves of vitex trifolia L. has anti-inflammatory property.